Use of real-time polymerase chain reaction to identify Entamoeba histolytica in schoolchildren from northwest Mexico - Sandra Aguayo-Patrón; Reyna Castillo-Fimbres; Luis Quihui-Cota; Ana María Calderón de la Barca (Journal of Infection in Developing Countries)
Introduction: Entamoeba histolytica, E. dispar, and E. moshkovskii are morphologically identical, but intestinal amebiasis is caused only by E. histolytica. Mexico is among the countries with high amebae infection rates, although the contribution of pathogenic amoeba to the total detected cases remains unknown, especially in the northwestern dry region. Therefore, the aim of this study was to identify the actual prevalence of E. histolytica using real-time polymerase chain reaction (PCR) in schoolchildren of  northwestern Mexico.